2016
DOI: 10.1016/j.gca.2015.11.044
|View full text |Cite
|
Sign up to set email alerts
|

Integrated single crystal laser ablation U/Pb and (U–Th)/He dating of detrital accessory minerals – Proof-of-concept studies of titanites and zircons from the Fish Canyon tuff

Abstract: Excimer laser technologies enable a rapid and effective approach to the simultaneous U/Pb geochronology and (U-Th)/He thermochronology of a wide range of detrital accessory minerals. Here we describe the 'laser ablation double dating' (LADD) method and demonstrate its viability by applying it to zircon and titanite crystals from the wellcharacterized Fish Canyon tuff. We found that LADD dates for Fish Canyon zircon (206 Pb/ 238 U-28.63 ± 0.11 Ma; (U-Th)/He-28.38 ± 0.73 Ma) are statistically indistinguishable f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 51 publications
(71 reference statements)
1
36
0
Order By: Relevance
“…Refinement of double-and triple-dating analytical procedures and expansion of these approaches to other detrital accessory phases is critical to this. For example, ongoing development of laser ablation (U-Th)/He thermochronometry and evaluation of method challenges will enable high sample throughput necessary for detrital studies in sedimentary rocks and modern drainage systems (e.g., Horne et al, 2016Horne et al, , 2019.…”
Section: 1029/2018tc005312mentioning
confidence: 99%
“…Refinement of double-and triple-dating analytical procedures and expansion of these approaches to other detrital accessory phases is critical to this. For example, ongoing development of laser ablation (U-Th)/He thermochronometry and evaluation of method challenges will enable high sample throughput necessary for detrital studies in sedimentary rocks and modern drainage systems (e.g., Horne et al, 2016Horne et al, , 2019.…”
Section: 1029/2018tc005312mentioning
confidence: 99%
“…The LADD method does not require an alpha ejection correction, and broken or noneuhedral grains can be analyzed (Tripathy‐Lang et al, 2013). The analytical procedures for zircon laser ablation (U‐Th)/He and U‐Pb analyses used in this study follow those of Horne et al (2016), who found that LADD methods yield results that are consistent with conventional whole‐crystal methods, but uncertainties are larger. The zircon grains were mounted in a puck using Torr Seal and then polished to erode 20–30 μm of the crystals.…”
Section: Methodsmentioning
confidence: 82%
“…The fields of detrital geochronology and thermochronology aim to identify the timing of crystallization and cooling of individual detrital mineral grains, respectively, with application to understanding both solid-earth (tectonic) and earth surface processes (Fedo, Sircombe, & Rainbird, 2003;Gehrels, 2012;Reiners & Brandon, 2006). Technological improvements over the last several decades, particularly in laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS), have led to greater efficiency in collecting detrital geochronologic data (Gehrels, 2014), and to a lesser extent thermochronologic data (Horne, van Soest, Hodges, Tripathy-Lang, & Hourigan, 2016). Although many detrital mineral types are used in geo-thermochronology, U-Pb and (U-Th)/He dating of detrital zircon (DZ) has emerged as a primary tool for constraining sediment provenance, refining palaeogeographic and tectonic interpretations, and constraining the depositional age of stratigraphic sequences (Fedo et al, 2003;Gehrels, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The trend towards a large-n sampling strategy (Daniels et al, 2017;Pullen, Ibáñez-Mejía, Gehrels, Ibáñez-Mejía, & Pecha, 2014) suggests that the quantity of detrital geochronologic data will continue to increase at a rapid pace. Although detrital thermochronologic datasets are typically smaller than their geochronologic counterparts, as a result of greater effort and expense of data collection, ongoing advances in He-dating using laser ablation shows promise in increasing the future quantity of detrital thermochronometric data (Horne et al, 2016).…”
Section: Introductionmentioning
confidence: 99%